Detection of Cathelicidin-1 and Cathelicidin-2 Biomolecules in the Milk of Goats and Their Use as Biomarkers for the Diagnosis of Mastitis - Maria V. Bourganou; Dimitra V. Liagka; Konstantinos Vougas; Daphne T. Lianou; Natalia G. C. Vasileiou; Konstantina S. Dimoveli; Antonis P. Politis; Nikos G. Kordalis; Efthymia Petinaki; Vasia S. Mavrogianni; George Th. Tsangaris; George C. Fthenakis; et al. (Animals)
The objectives of the present work were as follows: (i) the detection of cathelicidin biomolecules in the milk of individual goats during the early stages of mastitis and their potential use for the diagnosis of mastitis at its early stage and (ii) the evaluation of the presence of cathelicidin proteins in the bulk-tank milk from goat and sheep farms. In an experimental study, after inoculation of Staphylococcus simulans into a mammary gland of goats, bacteriological and cytological examinations of milk samples, as well as proteomics examinations [two-dimensional gel electrophoresis analysis (2-DE) and matrix-assisted laser desorption/ionization time-of-flight mass spectrometer (MALDI-TOF MS) analysis] were performed sequentially, from 4 to 48 h post-challenge. Cathelicidin-1 and cathelicidin-2 were detected consistently in milk samples obtained throughout the study, and spot optical densities obtained from PDQuest v.8.0 were recorded. Associations were calculated between the presence of mastitis in a mammary gland at a given timepoint and the detection of cathelicidin proteins in the respective milk sample. All inoculated mammary glands developed mastitis, confirmed by the consistent bacterial isolation from milk samples and the increased somatic cell content therein. Spot optical density of cathelicidin proteins was higher than in samples from contralateral mammary glands. There was a significant association between the presence of mastitis in a mammary gland and the detection of cathelicidin biomolecules in the respective milk sample; the overall accuracy was 81.8% (95% confidence interval: 70.4–90.2%). In a field investigation, the presence of cathelicidin proteins was evaluated in the bulk-tank milk of 32 dairy goat and 57 dairy sheep farms. In this part of the work, no cathelicidin proteins were detected in any bulk-tank milk sample of goat, 0.0% (95% confidence interval: 0.0–10.7%), or sheep, 0.0% (95% confidence interval: 0.0–6.3%), farms.